Characterising the epigenome as a key component of the fetal exposome in evaluating in utero exposures and childhood cancer risk - Ghantous, Akram (Mutagenesis, 2015)
Recent advances in laboratory sciences hold a promise for a ‘leap forward’ in understanding the aetiology of complex human diseases, notably cancer, potentially providing an evidence base for prevention. For example, remarkable advances in epigenomics have an important impact on our understanding of biological phenomena and importance of environmental stressors in complex diseases. Environmental and lifestyle factors are thought to be implicated in the development of a wide range of human cancers by eliciting changes in the epigenome. These changes, thus, represent attractive targets for biomarker discovery intended for the improvement of exposure and risk assessment, diagnosis and prognosis and provision of short-term outcomes in intervention studies. The epigenome can be viewed as an interface between the genome and the environment; therefore, aberrant epigenetic events associated with environmental exposures are likely to play an important role in the onset and progression of different human diseases. The advent of powerful technologies for analysing epigenetic patterns in both cancer tissues and normal cells holds promise that the next few years will be fundamental for the identification of critical cancer- and exposure-associated epigenetic changes and for their evaluation as new generation of biomarkers. Here, we discuss new opportunities in the current age of ‘omics’ technologies for studies with prospective design and associated biospecimens that represent exciting potential for characterising the epigenome as a key component of the fetal exposome and for understanding causal pathways and robust predictors of cancer risk and associated environmental determinants during in utero life. Such studies should improve our knowledge concerning the aetiology of childhood cancer and identify both novel biomarkers and clues to causation, thus, providing an evidence base for cancer prevention.